Quick hits in emergency medicine - Allen, Brandon (Springer New York, 2013)
For important information you need to know, but can't remember, turn to QUICK HITS IN EMERGENCY MEDICINE.  This practical, short compendium contains the key decision-rules, clinical values, mnemonics, and dosages that you need at your finger tips in the ED.   It covers everything from acute coronary syndrome and ACLS, to electrolyte equations and hyperkalemia, to ventilator settings by disease to Wellen's syndrome.  Information on each topic is limited to a single page and presented in easily digested formats such as tables, algorithms, bulleted lists, and clinical illustrations.